PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN PRODUKTIVITAS DI INDUSTRI KREATIF - Oktavia Anggraini; Hendra Riofita (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2024)
Effective human resource management (HRM) plays a crucial role in creating a supportive work environment, attracting top talent, and motivating employees for optimal performance. The creative industry, which has evolved significantly with advancements in information and communication technology, highlights HRM's importance. Initially thriving in developed nations, the creative industry concept has expanded to developing countries, including Indonesia. Utilizing information technology in this sector enhances public awareness of its role in driving economic growth. This study, based on a literature review, explores the development of the creative industry and its reliance on intellectual property to generate economic value, foster prosperity, and create jobs. Community involvement and enthusiasm also play vital roles in advancing this industry. HRM's strategic contributions to the creative industry include competency development, performance management, and cultivating eco-friendly work environments. These initiatives not only boost employee productivity but also drive organizational growth. In the global competitive landscape, effective HRM is indispensable for maximizing employee potential and ensuring the creative industry's success. By prioritizing innovation, skill enhancement, and strategic resource allocation, HRM serves as the foundation for sustainable development in this sector.